2020
DOI: 10.1016/j.jcrs.2019.09.003
|View full text |Cite|
|
Sign up to set email alerts
|

Transient effect of suction on the retinal neurovasculature in myopic patients after small-incision lenticule extraction

Abstract: Purpose: To characterize retinal neurovasculature changes after small-incision lenticule extraction (SMILE) in myopic patients. Setting: Ophthalmic Center, the Second Affiliated Hospital of Guangzhou Medical University, China. Design: Prospective interventional study. Methods: The corrected distance visual acuity/uncorrected distance visual acuity, corrected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…7 Studies have shown that OCTA has low intravisit and intervisit blood flow index and vascular density variability. 15,20 Our findings demonstrated that the macular and peripapillary retinal microvascular networks were significantly reduced in SLE patients with longer disease durations, compared with NCs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…7 Studies have shown that OCTA has low intravisit and intervisit blood flow index and vascular density variability. 15,20 Our findings demonstrated that the macular and peripapillary retinal microvascular networks were significantly reduced in SLE patients with longer disease durations, compared with NCs.…”
Section: Discussionmentioning
confidence: 59%
“…To evaluate the thickness of ganglion cell-inner plexiform layer (GCIPL) and peripapillary retinal nerve fiber layer, Zeiss Cirrus Angioplex OCTA (Carl Zeiss Meditec, Dublin, CA) was used to perform high-definition OCT, with a 512 × 128 scanning protocol. As described previously, 15 GCIPL thickness was measured using elliptic partitions, whereas peripapillary retinal nerve fiber layer thickness was measured using quadrant partitions. The measurements were acquired from OCT reports (see Figure , Supplemental Digital Content 2 , http://links.lww.com/IAE/C138).…”
Section: Methodsmentioning
confidence: 99%
“…In the study by Liu et al, 1 they evaluated retinal tomography and vascular features after small-incision lenticule extraction. The postoperative evaluation was performed at day 1 and day 7.…”
mentioning
confidence: 99%